Efficacy of 5-Aminosalicylic Acid Enemas in the Treatment of Distal Ulcerative Colitis - MG Robinson; DL Decktor (Canadian Journal of Gastroenterology)
The efficacy of 4 g 5-aminosalicylic acid (5-ASA, mesalamine) enemas was assessed in 666 patients with distal ulcerative colitis. Patients were enrolled in an open-label compassionate use program. One 4 g 5-ASA enema was administered each night for a period of four weeks and the disease activity index was assessed at baseline and on days 14 and 28. On days 14 and 28, 78.0% and 88.1% of patients, respectively, demonstrated an improvement in disease activity index. The mean decline in disease activity index on day 14 was 40.7% (P=0.0001) and on day 28 it was 55.4% (P=0.0001). Efficacy was similar whether the disease was confined to or extended beyond 30 cm from the anus. There was no difference in efficacy in patients suffering their first episode of disease compared to patients suffering subsequent attacks. In conclusion, high dose 5-ASA enemas are a highly effective treatment for distal ulcerative colitis.